Wind-driven nearshore overturning currents off the northeastern Shandong Peninsula in the Yellow Sea in winter - Hu, Luoyu; Zhai, Fangguo; Liu, Zizhou; Gu, Yanzhen; Wu, Wenfan; Li, Peiliang; Liu, Jianying; Ding, Jinqiang; Sun, Liyuan (Frontiers in Marine Science, 2024)
Introduction The nearshore sea off the northeastern Shandong Peninsula is characterized by intensive mariculture, whose ecosystem is involved in the large marine ecosystem of the Yellow Sea. However, ocean currents in this area are poorly explored. Observations suggested overturning currents were robust phenomena in winter in this area. Methods Numerical simulations and experiments were used to investigate the mechanisms of overturning currents. Results There were two classes of wind-driven overturning currents. One consisted of surface southeastward currents, nearshore downwelling currents, and bottom northeastward currents. The other consisted of surface northeastward currents, nearshore upwelling currents, and bottom southwestward currents. Discussion The underlying dynamics involved local wind forcing and propagation of coastal trapped waves (CTWs). Northwesterly winds in the Bohai Sea and North Yellow Sea drove surface southward currents and converged water toward coastline off the northeastern Shandong Peninsula, generating nearshore sea level rising. The resultant southward sea level slope drove nearshore bottom northward currents. Meanwhile, high sea level in the southern part of Bohai Sea and North Yellow Sea also propagated as CTWs clockwise around the Shandong Peninsula, which further enhanced nearshore bottom northward currents and caused eastward currents in the entire water column off the northeastern Shandong Peninsula. Southwesterly winds in the Bohai Sea and North Yellow Sea drove surface northward currents, generating nearshore sea level dropping off the northeastern Shandong Peninsula. The resultant northward sea level slope caused bottom southward currents. Meanwhile, the southwesterly winds caused CTWs with low sea level in the south part of the Bohai Sea and Yellow Sea. The northward sea level slope of CTWs enhanced nearshore bottom southwestward currents. The current study emphasized winds in winter drove not only local currents but also propagation of CTWs in the Bohai Sea and North Yellow Sea. The sea level slope of CTWs regulated surface and bottom Ekman layers driven by local winds.